Buzzkill : a wild wander through the weird and threatened world of bugs - Maloney, Brenna (Godwin Books : Henry Holt and Company, 2022)
First person narrative by the author offers a wealth of facts and information about insects and explores the vital function that insects play in the world, from their role as pollinators and recyclers to their potential as a nutritious and sustainable food source. Includes a suggested reading list for further information.